2003
DOI: 10.1074/jbc.m302816200
|View full text |Cite
|
Sign up to set email alerts
|

Rh-RhAG/Ankyrin-R, a New Interaction Site between the Membrane Bilayer and the Red Cell Skeleton, Is Impaired by Rhnull-associated Mutation

Abstract: Several studies suggest that the Rh complex represents a major interaction site between the membrane lipid bilayer and the red cell skeleton, but little is known about the molecular basis of this interaction. We report here that ankyrin-R is capable of interacting directly with the C-terminal cytoplasmic domain of Rh and RhAG polypeptides. We first show that the primary defect of ankyrin-R in normoblastosis (nb/nb) spherocytosis mutant mice is associated with a sharp reduction of RhAG and Rh polypeptides. Seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
109
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(114 citation statements)
references
References 43 publications
4
109
0
1
Order By: Relevance
“…Of note, the expression level of RhAG in transfected HEK-293 cells (9500 copies of RhAG/ cell) is lower than that observed in Rh null RBCs of the amorph type (17 000 copies of RhAG/RBC) which already exhibited much reduced alkalinization rate constant values, as compared with normal control RBCs (100 000 copies of RhAG/cell) [20]. Accordingly, the alkalinization rate constant value of HEK-293 cells submitted to an inwardly directed ammonium gradient was not modified by the low expression level of RhAG which is presumably due to the absence in HEK-293 cells of the RhAG protein partners present in RBCs, i.e Rh (D and CE) [3], ankyrin R [38] and Band 3 [39], which are necessary for its full membrane expression.…”
Section: Discussionmentioning
confidence: 79%
“…Of note, the expression level of RhAG in transfected HEK-293 cells (9500 copies of RhAG/ cell) is lower than that observed in Rh null RBCs of the amorph type (17 000 copies of RhAG/RBC) which already exhibited much reduced alkalinization rate constant values, as compared with normal control RBCs (100 000 copies of RhAG/cell) [20]. Accordingly, the alkalinization rate constant value of HEK-293 cells submitted to an inwardly directed ammonium gradient was not modified by the low expression level of RhAG which is presumably due to the absence in HEK-293 cells of the RhAG protein partners present in RBCs, i.e Rh (D and CE) [3], ankyrin R [38] and Band 3 [39], which are necessary for its full membrane expression.…”
Section: Discussionmentioning
confidence: 79%
“…4 Recent findings indicate that Rh proteins mediate key interactions with the underlying cytoskeleton through protein 4.2 and ankyrin. [5][6][7] The erythrocyte Rh blood group proteins are well known because of their importance in blood transfusion, but recent functional studies and structural modeling reveal that the Rh blood group proteins are members of an ancient family of proteins involved in ammonia transport. [8][9][10][11] Non-erythroid Rh proteins have now been found in other tissues including the kidney, liver, brain, and skin 12-15 , in locations where ammonia production and elimination occurs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the well described band 3-ankyrin-protein 4.2 and glycophorin C-protein 4.1-p55 complexes (6), the Rh complex represents a major interaction site between the membrane lipid bilayer and the spectrin-based cytoskeleton. Indeed, recent studies of the erythroid ankyrin-deficient normoblastosis mice and analysis with the yeast two-hybrid system have shown that Ank1 may interact directly with the C-terminal cytoplasmic domains of Rh protein and RhAG (7). Interestingly, in humans this interaction was abolished by a mutation found in an Rh null patient (7).…”
mentioning
confidence: 99%